Ludwigs Angina: lessons learned. (24th May 2012) - Brotherton, H; Montague, ML; Rowney, D; Templeton, K
Abstract : Introduction: Ludwigs Angina is a rapidly progressive gangrenous cellulitis of the submandibular space historically associated with a high mortality rate due to airway obstruction. In 90% of adults the aetiology is odontogenic whilst in children an odontogenic source accounts for a third of cases. The microorganisms implicated include a range of bacteria, particularly streptococcal species, gram-negative rods and anaerobes. Objective: This clinical case presentation aims to highlight the lessons learnt in the management of a young child with Ludwig's Angina. Population and Methods: A previously well 13-month-old girl presented with pyrexia and acute swelling of the neck and floor of mouth following a coryzal illness. Intravenous antibiotic therapy was commenced at her local hospital. Despite this she deteriorated rapidly with increasing respiratory compromise requiring intubation and transfer to the regional PICU. We describe her further conservative yet aggressive management with steroids, antibiotics and conservative ENT care in a tertiary care setting. Results: Neck ultrasound showed extensive subcutaneous oedema with no focal abscess. A clinical diagnosis of Ludwig's Angina was made after specialist paediatric ENT assessment. The neck swelling and upper airway oedema improved but her clinical course was complicated by lower respiratory tract infection. Tracheal secretions were positive for parainfluenzae type 3. Haemophilus influenzae and Moraxella catarrhalis were isolated from bronchoalveolar lavage fluid. In total she required PICU care for 7 days and ventilatory support for 5 days. Conclusions: Valuable lessons can be learned from this clinical case: (1) Ludwigs Angina has a typical bull neck appearance with diffuse brawny swelling of the neck. (2) It is a cause of acute rapidly progressive airway obstruction and may present as a life threatening airway emergency. (3) It may be complicated by contiguous spread of infection within the respiratory tract. (4) Viral upper respiratory tract infection followed by Gram negative bacterial infection is a recognised infectious aetiology with the viral infection facilitating polymicrobial infection. Microbiological diagnosis is helpful to guide prognosis as well as management. (5) Early recognition of this soft tissue cellulitis is essential for prompt airway and antibiotic management.